Incidence, Impact, and Management of Incidentalomas on Preoperative Computed Tomographic Angiograms for Breast Cancer Patients with and without Genetic Mutations. Issue 6 (10th May 2021) - Lu, Stephen M.; Waldman, Leah E.; Boudiab, Elizabeth M.; Lopez, Christopher D.; Bassiri-Tehrani, Brian; DelMauro, Matthew A.; Israeli, Ron; Bank, Jonathan; Machnicki, Stephen C.; Lerman, Oren Z.
Abstract : Background: Preoperative abdominal computed tomographic angiograms for free flap breast reconstruction improve operative safety and efficiency, but incidental findings are common and potentially affect management. In addition, the authors hypothesized that patients with genetic mutations might have a higher rate of significant findings. The authors present the largest series of computed tomographic angiogram "incidentalomas" in these two populations and an evidence-based algorithm for managing common findings. Methods: All patients undergoing free flap breast reconstruction at Northwell Health between 2009 and 2017 were eligible. Medical history, perioperative details, and radiology reports were examined with abnormal findings recorded. Published literature was reviewed with radiologists to develop standardized guidelines for incidentaloma management. Results: Of 805 patients included, 733 patients had abdominal imaging. One hundred ninety-five (27 percent) had a completely negative examination. In the remaining 538 patients, benign hepatic (22 percent) and renal (17 percent) findings were most common. Sixteen patients (2.2 percent) required additional imaging ( n = 15) or procedures ( n = 5). One finding was concerning for malignancy—renal cell carcinoma—which interventional radiology ablated postoperatively. Seventy-nine patients (10.8 percent) had a genetic mutation but were not found to have a statistically significant higher rate of incidentalomas. Conclusions: The authors' rate of computed tomographic angiography incidental findings (73 percent) is consistent with previous studies, but the rate requiring further intervention (2.2 percent) is lower. Incidental findings were no more common or pathologic among genetic mutation carriers. The authors also introduce an evidence-based algorithm for the management of common incidentalomas. Using these guidelines, plastic surgeons can reassure patients, regardless of mutation status, that incidentalomas are most commonly benign and have minimal impact on their surgical plan.